Industrial Training Report: Perpustakaan Hamdan Tahir, Universiti Sains Malaysia / Bibi Auni Mohamad - Mohamad, Bibi Auni (Faculty of Information Management, 2018)
To complete my study, this training is needed to be complete for 5 months internship. Hamdan Tahir Library at Universiti Sains Malaysia Kubang Kerian, Kelantan is the organizntion that has been selected by the trainee. The training at Ham:lan Tahir Library is giving an opportunity for the trainee to learn about the hbrary management. The librarian is prepared a schedule for the trainee to learn important task and do special project at Hamdan Tahir Library. The trainee learns how to improve communication skills, learn how to be more punctual and discipline. Other than that, the trainee also has gained knowledge, skills and experience during the training. Besides that, the practical training exposed the student to the real working experience.